Performance and emission characteristics of a diesel engine using Calophyllum Inophyllum biodiesel blends with TiO2 nanoadditives and EGR - A. Praveen; G. Lakshmi Narayana Rao; B. Balakrishna (Egyptian Journal of Petroleum)
An experimental investigation was carried out to evaluate the performance and emission characteristics of a single cylinder diesel engine by using Calophyllum Inophyllum biodiesel blends with TiO2 nano additives and exhaust gas recirculation (EGR). The Calophyllum Inophyllum biodiesel-diesel blend was prepared by mixing 20% of Calophyllum Inophyllum biodiesel with 80% diesel (B20) in volumetric approach. The TiO2 nanoparticles were dispersed into a B20 fuel with a dosage of 40 ppm to prepare the B2040TiO2 fuel sample. The tests were conducted on a diesel engine by using B20, B2040TiO2, B20 + 20%EGR, B2040TiO2 + 20% EGR fuel samples at different load conditions. The brake thermal efficiency of B2040TiO2, B2040 TiO2 + 20%EGR fuels increased by 3.1%, 2.5%, and decreased by 1.8% for B20 + 20%EGR fuel compared to the B20 fuel at full load condition. The CO and HC emissions were reduced with the addition of TiO2 nano particles to the B20 fuel and increased with the EGR method compared to the B20 fuel. The smoke emissions were increased by 16.23% and 12% for the B20 + 20%EGR and B2040TiO2 + 20%EGR fuel samples compared to the B20 fuel at full load condition. The NOx emissions were reduced with the EGR technique and increased with the addition of TiO2 nanoparticles to the biodiesel blend compared to the B20 fuel. It is concluded that Calophyllum Inophyllum biodiesel blend (B20) with the addition of TiO2 nano particles and EGR technique exhibits better engine performance and reduced emissions compared to the other fuels. Keywords: Combustion, Performance, Emission, Exhaust gas recirculation, TiO2 nano particles, Calophyllum Inophyllum biodiesel